Sleep, Performance, and Memory in Flies. - Dissel, S.; Melnattur, K.; Shaw, P.J. (Current sleep medicine reports, 2015)
Drosophila has proven to be a powerful model to identify genes and circuits that impact sleep. While the majority of studies have primarily been interested in identifying manipulations that alter sleep time, a growing body of work has begun to focus on how changing sleep influences functional outcomes such as cognitive performance, structural plasticity, and metabolism to name a few. Evaluating sleep time provides an appropriate entry point into elucidating sleep function. However, it is not possible to fully understand how a manipulation has impacted sleep regulation without first establishing how it has affected the animals' well-being. Synaptic plasticity and memory are important functional outcomes that can be used to asses an animal's status. In this manuscript, we review recent advances in studies examining sleep, memory, and performance. We conclude that as Drosophila sleep researchers expand their analysis beyond sleep time, the opportunities to discover the function of sleep will be enhanced.